The Influence of Motivational Training on Learning Achievement in Students - Amanda, Resi Suci; Rahni Rismawati; M Najarudin Rizki (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
This research aims to examine the effect of motivational training on the academic achievement of psychology students at UIN Raden Fatah Palembang. A total of 30 students were selected using probability sampling techniques, and a pretest-posttest design was used in this research. The results show that motivational training does not have a significant effect in improving academic achievement. The pretest scores show a normal distribution, but the posttest scores are not normal. In addition, the correlation between pretest and posttest is very low. Therefore, further research is needed with a larger sample and different methods to validate the findings of this study.